The common good and Christian ethics - Hollenbach, David (New studies in Christian ethics ;, 2002)
The Common Good and Christian Ethics rethinks the ancient tradition of the common good in a way that addresses contemporary social divisions, both urban and global. David Hollenbach draws on social analysis, moral philosophy, and theological ethics to chart new directions in both urban life and global society.